Anti-inflammatory and immunomodulatory properties of Mentha piperita green-formulated gold nanoparticles and its effect on ovalbumin-induced asthma and lung pathological changes in rats. Issue 1 (31st December 2022) - Yi, Wenxia; Chen, Ruidong; Xie, Fei; Xu, Chunyan; Tian, Wenqiu
Abstract: Regarding applicative, facile, green chemical research, a bio-inspired approach is being reported for the synthesis of Au nanoparticles by Mentha piperita as a natural reducing and stabilising agent in alkaline medium without using any toxic reducing agent. The biosynthesized Au NPs@ Mentha piperita were characterised by advanced physicochemical techniques like ultraviolet-visible (UV-Vis), Fourier Transformed Infrared spectroscopy (FT-IR), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), Energy Dispersive X-ray spectroscopy (EDX), and X-ray Diffraction (XRD) study. It has been established that Au NPs@ Mentha piperita have a spherical shape with a mean diameter from ∼10 nm. To survey the cytotoxicity effects of Au NPs@ Mentha piperita, MTT assay was used on HUVEC cell line. To survey the antioxidant properties of Au NPs@ Mentha piperita, the DPPH test was used in the presence of butylated hydroxytoluene as the positive control. The Au NPs@ Mentha piperita inhibited half of the DPPH molecules in the concentration of 113 µg/mL. In the in vivo, wistar rats were divided to four groups; non-sensitised, sensitised to ovalbumin, sensitised and treated with dexamethasone (1.25 μg/mL), and Au NPs@ Mentha piperita (5 μg/mL) in drinking water for 21 days. The levels of total protein (TP), phospholipase A2 (PLA2 ), immunoglobulin E (IgE), IFN-γ/IL-4 ratio, interferon gamma (IFN-γ), and interleukin 4 (IL-4) in BALF, and lung pathological changes were examined. A significant increase in PLA2, IgE, IL-4, and TP levels, all lung pathological indices as well as significant decrease in IFN-γ/IL-4 ratio was seen in the asthmatic compared to the control rats. Treatment with Au NPs@ Mentha piperita (5 μg/mL) resulted in decreased PLA2, IgE, IL-4, and TP levels, but increased IFN-γ/IL-4 ratio compared to untreated sensitised rats. The Au NPs@ Mentha piperita significantly improved the pathological changes of sensitised rats. The improvement effects of higher concentrations of the Au NPs@ Mentha piperita extract were significantly more than those of dexamethasone. The improvement effects of Au NPs@ Mentha piperita on pathological changes, immunological and inflammatory markers in sensitised rats comparable or even more potent than dexamethasone suggests the therapeutic potential of the nanoparticle in asthma. After confirming these results in clinical trial studies, Au NPs@ Mentha piperita can be used as a new drug for the treatment of asthma in humans.